Challenges and support needs among persons with a migration background who use drugs in four European metropolitan cities - Aline Pouille; Clara De Ruysscher; Lena van Selm; Jan van Amsterdam; Wim van den Brink; Machteld Busz; Roberto Perez Gayo; Marios Atzemis; Wouter Vanderplasschen; the SEMID-EU consortium (BMC, 2024)
Abstract Background Persons who migrate for economic reasons, along with asylum seekers and refugees, face multiple personal experiences and societal inequalities that increase the risk of mental health problems and substance dependency, compounded by intersectional social and economic vulnerabilities. The precarious situation and limited access to care of persons with a migration background who use drugs (PMWUD) in Europe raises concern. Therefore, this qualitative study explores the challenges and support needs of a sample of PMWUD in vulnerable situations living in Amsterdam, Athens, Berlin and Paris. Methods This study employed a community-based participatory approach. Through semi-structured interviews with PMWUD (n = 99), we identified  (service) needs of a diversity of PMWUD in Europe. Participants were recruited through a combination of community gatekeepers, venue-based sampling, and snowball sampling. Trained community researchers conducted the interviews, which focused on participants' living situation, substance use, physical and mental health, and employment opportunities. Results Despite substantial heterogeneity among the PMWUD, several common themes emerged across all groups. Participants frequently mentioned early childhood adversity, limited social networks leading to loneliness, medical, psychological, and substance use issues, histories of personal violence or poverty, homelessness, lack of necessary documents for health care, social security, and employment, and encounters with the criminal justice system. These intertwined and mutually reinforcing factors simultaneously functioned as barriers to care and support, alongside other barriers such as linguistic and cultural differences, and stigma and discrimination. Due to social exclusion, migration, and substance dependence, participants had limited reliable social networks. Therefore, they often had to rely on accessible and low-threshold services. Harm reduction services played a significant role in providing support to PMWUD. Most PMWUD indicated that basic needs for hygiene and food were met thanks to local organizations. Differences in housing opportunities and access to harm reduction services were identified in each city. Conclusion Structural barriers toward treatment and care, often related to administrative requirements, stand in the way of appropriate care for PMWUD. Linguistically and culturally sensitive outreach activities with limited practical requirements could break down social and treatment barriers.